Glucose homeostasis in statin users—The LIFESTAT study. Issue 3 (21st December 2018) - Morville, Thomas; Dohlmann, Tine; Kuhlman, Anja B.; Monberg, Tine; Torp, Mimmi; Hartmann, Bolette; Holst, Jens J.; Larsen, Steen; Helge, Jørn W.; Dela, Flemming
Abstract: Background: Statins are widely used to lower cholesterol concentrations in both primary and secondary prevention of cardiovascular disease. The treatment increases the risk of muscle pain (myalgia) and of type 2 diabetes. However, the underlying mechanisms remain disputed. Methods: We investigated whether statin induced myalgia is coupled to impaired glucose homeostasis using oral glucose tolerance test (OGTT), intravenous glucose tolerance test (IVGTT), and the hyperinsulinemic euglycemic clamp. We performed a cross‐sectional study of statin users without CVD (primary prevention) stratified into a statin myalgic (M; n  = 25) and a non‐myalgic (NM; n  = 39) group as well as a control group (C; n  = 20) consisting of non‐statin users. Results: A reduction in the insulin secretion rate during the OGTT was observed in the myalgic group compared with the non‐myalgic group (AUC ISROGTT, C: 1032 (683 ‐ 1500); M: 922 (678 ‐ 1091); NM: 1089 (933 ‐ 1391) pmol·L −1 ·min (median with 25%‐75% percentiles), but no other measurements indicated impaired β‐cell function. We found no other differences between the three groups for other measurements in the OGTT, IVGTT, and euglycemic clamp. Muscle protein content of GLUT4 and hexokinase II was similar between the three groups. Conclusions: We conclude that statin users in primary prevention experiencing myalgia do not have impaired glucose homeostasis compared with other statin users or non‐users. We consider this an important aspect in the dialogue between physician and patient regarding statin treatment and adverse effects.